2019
DOI: 10.3171/2018.8.spine18517
|View full text |Cite
|
Sign up to set email alerts
|

Repeated recurrence of thoracic spine stenosis following decompression alone for ossification of the ligamentum flavum: case report

Abstract: Ossification of the ligamentum flavum (OLF) is a well-recognized but rare cause of thoracic myelopathy. Its subtle and variable clinical presentation often makes the diagnosis challenging. The treatment of symptomatic OLF requires surgical intervention, with the most common surgical procedure being a posterior decompression with or without instrumentation. Recurrence of ossification and stenosis after surgery is rare and usually occurs at the same intervertebral level. Multiple recurrences of ossificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Because OLF progresses from the lateral to the medial part of the ligamentum flavum 35) , removal of OLF from the medial to lateral part with preservation of the facet joint may leave the lateral part of OLF. This remained OLF may grow due to micro-motion and tensile stress at the operated segment 2,35) , and the recurrence of OLF has been reported after decompression-only surgery 3,6,14,30,44) . To date, there has been no reported case of recurrence at the surgical site after instrumented fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Because OLF progresses from the lateral to the medial part of the ligamentum flavum 35) , removal of OLF from the medial to lateral part with preservation of the facet joint may leave the lateral part of OLF. This remained OLF may grow due to micro-motion and tensile stress at the operated segment 2,35) , and the recurrence of OLF has been reported after decompression-only surgery 3,6,14,30,44) . To date, there has been no reported case of recurrence at the surgical site after instrumented fusion.…”
Section: Discussionmentioning
confidence: 99%
“…OLF is shown as the primary cause of thoracic myelopathy (13)(14)(15)(16). The studies have reported that OLF is more common in the fifth and sixth decades of life, its incidence increases with age, and it is seen at a higher rate in East Asian countries, especially in Japanese people (4,14,(17)(18)(19). In many studies, factors such as genetics, dietary habits, mechanical stress, and cytokine production in the ligamentum flavum have been implicated in the etiology of OLF, and no definitive etiological factor has been reported (7).…”
Section: Discussionmentioning
confidence: 99%
“…Since neurological symptoms mostly affect the lower extremities, TSS can be confused with lumbar spinal pathologies and patients may be clinically misdiagnosed (2,10). Generally, patients present to the clinic with symptoms of progressive thoracic myelopathy, back pain, and/or signs of acute severe paraparesis or paraplegia after minor trauma (4)(5)(6)11).…”
Section: Introductionmentioning
confidence: 99%
“…Decompression itself can be very challenging since the flavum is fused with the laminae above and below and it becomes very difficult for the surgeon to insert Kerrison roungers in inter-laminar space that is uncertain due to the low prevalence of disease and inconstant pre-operative status thus is invaluable for further research. Recurrence of OLF leading to thoracic myelopathy has been reported in the literature after laminectomy at the same intervertebral level [4,5] but no case of adjacent level OLF in thoracic spine reported yet. We report a case of a 37-year-old male who was already operated for thoracic myelopathy secondary to OLF at D8-D9 level 4 years ago and now presented with gait abnormality due to OLF at D6 to D8 level with coexisting asymptomatic L1-2 disc prolapse.…”
Section: Introductionmentioning
confidence: 98%